2019
DOI: 10.1038/s41598-019-46706-7
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing nutrient recycling from excreta to meet crop nutrient needs in Sweden – a spatial analysis

Abstract: Increased recycling of nutrient-rich organic waste to meet crop nutrient needs is an essential component of a more sustainable food system. However, agricultural specialization continues to pose a significant challenge to balancing crop nutrient needs and the nutrient supply from animal manure and human excreta locally. For Sweden, this study found that recycling all excreta (in 2007) could meet up to 75% of crop nitrogen and 81% of phosphorus needs, but that this would exceed crop potassium needs by 67%. Recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Figure 2 below showcases that the N that could be recovered from municipal wastewater and MOW produced by 77,250 people could cover the net N-fertilizer demand of the entire vegetable production of Vienna; recoverable P even exceeds the demand, while K must be added from another source. Consistent with previous research, availability of K is relatively low in human excreta (e.g., [1]), and consistently in overall treated municipal wastewater (e.g., [6]). K could be supplemented with sustainable and cheap K sources such as biomass ash or Fig.…”
Section: Linking Recoverable Npk To Crop Nutrient Demandsupporting
confidence: 89%
“…Figure 2 below showcases that the N that could be recovered from municipal wastewater and MOW produced by 77,250 people could cover the net N-fertilizer demand of the entire vegetable production of Vienna; recoverable P even exceeds the demand, while K must be added from another source. Consistent with previous research, availability of K is relatively low in human excreta (e.g., [1]), and consistently in overall treated municipal wastewater (e.g., [6]). K could be supplemented with sustainable and cheap K sources such as biomass ash or Fig.…”
Section: Linking Recoverable Npk To Crop Nutrient Demandsupporting
confidence: 89%
“…Therefore, it is essential for organic farming development to identify new and better organic fertilizers that both minimize crop yield losses and enhance soil quality during the conversion period. Traditional organic fertilizers mainly include human excreta ( Akram et al, 2019 ), compost, and poultry manure ( Guo et al, 2016 ; Liu et al, 2016 ). Ecologists have suggested more available, effective, and cheaper organic fertilizers to completely or partially replace chemical fertilizers, such as different types of straw ( Yang et al, 2015 ; Zhao et al, 2018 ), biochar ( Zhang et al, 2020 ), sewage sludge, and municipal solid waste ( Tejada & Benítez, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of other countries using human excrement as a potential source for organic fertilizer (Low-tech magazine, 2010). Japan, China, and Sweden are some countries using human excrement as a source of fertilizer in agriculture (Low, 2013;Carlton et al, 2015;Akram et al, 2019). A study carried out in Sweden to enhance nutrient recycling from human and animal excrement reported that recycling excrement enhances plants' nutrient availability and could reduce the dependency on synthetic fertilizers and lead to sustainability (Akram et al, 2019).…”
Section: Human Excreta Compostingmentioning
confidence: 99%
“…Japan, China, and Sweden are some countries using human excrement as a source of fertilizer in agriculture (Low, 2013;Carlton et al, 2015;Akram et al, 2019). A study carried out in Sweden to enhance nutrient recycling from human and animal excrement reported that recycling excrement enhances plants' nutrient availability and could reduce the dependency on synthetic fertilizers and lead to sustainability (Akram et al, 2019). Thus, a traditional practice combined with modern scientific knowledge, including microbiological interventions and engineering the toilet structures, can prove to be more efficient and acceptable in attaining a sustainable future in the mountain ecosystem.…”
Section: Human Excreta Compostingmentioning
confidence: 99%